DIVERSIFICAÇÃO E EVOLUÇÃO DOS CROMOSSOMOS SEXUAIS ZZ/ZW NO GÊNERO Characidium - Pucci, Marcela Baer (2013)
The Characidium genus is the biggest and most diversified within the Characidiinae subfamily. Broadly distributed throughout Neotropical region, Characidium possesses 53 available species. These fishes mostly showed a karyotypic diploid number equal 50 chromosomes, with a karyotypic formula usually 32m+18sm. The genus is extremely interesting for genetic studies, due to the existence of several variations as the supernumerary or B chromosomes in some populations, the occurrence of natural triploidy, different positions and number of rDNA, sex chromosomes size and morphology variation, when they are present. In this work, the C. zebra, C. cf. zebra,C. aff. zebra, C. pterostictum, Characidium sp., C. heirmostigmata e C.gomesi species were karyotypically characterized. In addition, the C. gomesi W sex chromosome probe was obtained, through chromosome microdissection and afterward chromosome painting in other species. Simultaneously, 18S and 5S rDNA sites were located. The conventional species analysis proved the existence of the standard diploid number for the genus, 2n=50 chromosomes. Through C banding technique, it was verified the absence of the sex chromosome system ZZ/ZW, due to the lack of heterochromatic W chromosome, in the C. zebra, C. cf. zebra and C. aff. zebra populations. In C.pterostictum the sex chromosome system is in the beginning of the heterochromatinization process and in the Characidium sp., C. heirmostigmata and C.gomesi, the system is found totaly differentiated, showing the W chromosome completely heterochromatic. The comparative chromosome painting with the C.gomesi W- specific probe in the other species detected the sex chromosomes of C.pterostictum, Characidium sp., C. heirmostigmata and C. gomesi. With the W-specific probe the repetitive regions blocks were located in some chromosomes of all the analyzed species, showing a probable common origin of these repetitive regions and sex chromosome. The rDNA sites showed species-specific distribution, varying in amount and location. It has already been determined that the 45S rDNA was involved in the differentiation of the Characidium sex chromosome pair. The chromosomal evidences showed that the nucleolar organizing regions (NOR) carrier pair translocated with another autosome to form the proto sex chromosome pair of the genus. Afterward occurred an intense W chromosome heterochromatinization. In some species the NOR suffered a new transposition to another autosome pair, shared condition in species with extensive W chromosome heterochromatinization. Moreover, some species evidenced an increasing in the number of the 45S and 5S rDNA. Thus, the modifications associated to the differentiation of the sex chromosomes and number and position of the rDNA have been the main agents of the chromosomal evolution in Characidium. In this work, it was also possible verify that the biogreographic isolation, mainly in the rivers headwater and population differentiation are closely associated with the speciation in the group, afterward with sex chromosome system diversification and probable reproductive/chromosomal barrier arising among population/species.